Ejaculation Preserving Technique in TURP Is it safe? - Mohammed Saeed Alkumait, Mohanned Hussam (Diyala Journal of Medicine, 2018)
Background: The treatment of bladder outlet obstruction in patients diagnosed with benign prostatic hyperplasia using the transurethral resection of the prostate procedure often presents with retrograde ejaculation as a complication due to bladder neck stenosis. Objective:To determine the safety and ease of use of the ejaculation preservation technique of the transurethral resection of the prostate procedure. Patients and Methods: The study was done in Samarra city in Iraq, included 30 patients between the ages of 50 and 62 years. The resection of the prostate was done a centimeter above the verumontanum in order to preserve the paraculcular tissue. The patients were assessed for the degree of ejaculate using the Ejaculation Projection Score. The patients were also evaluated for erectile function using the International Index of Erectile Function and for urinary retention using the International Prostate Symptom Score. The assessments were done preoperative, 4 months and 36 months after the ejaculation-preserving transurethral resection of the prostate procedure. Results: The maximum flow rate increased from 5.4ml/s to 21±5.2ml/s (n=29, p-value<0.001). IPSS improve from 24 to 5±2.5 (n=29, p-value<0.001). The quality of life score improved from 5.7 to 1.4±1.0 (n=29, p-value<0.001). The residual urine volume reduced from 150ml to 23± 14 (n=29, p-value<0.001). The erectile function reduced from 4 to 3.7 while the EPS reduced from 3.5±0.5 to 3.3+-0.5 (p-value=0.57). 96.7% of the patients ejaculated postoperatively. Statistical analysis was done with SPSS version 15 for windows, P value and T test for significance of results being P value < 0.05. Conclusion: There is evidence to show that the ejaculation preserving technique of the transurethral resection of the prostate is safe and secure to use. It protects anterograde ejaculation while reducing urine retention.